1999
DOI: 10.1177/107110079902001210
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented Measurement of Anteroposterior and Inversion-Eversion Laxity of the Normal Ankle Joint Complex

Abstract: Manual examination is the most common method for the evaluation of ankle anteroposterior (AP) and inversion-eversion (I-E) laxity. Objective assessment data of normal ankle laxity must be provided before comparison with an injured ankle can be made. The purpose of this study was to compare AP translation and I-E rotation at three force loads between dominant and nondominant ankles and to assess the test-retest reliability of a portable arthrometer in obtaining these measurements. The arthrometer consists of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
95
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 25 publications
10
95
1
Order By: Relevance
“…[1][2][3] Valid and reliable measurements of the combined motions within the talocrural and subtalar joints (ankle complex) have been investigated fully and reported using the Hollis Ankle Arthrometer (Blue Bay Research, Inc, Navarre, FL). [3][4][5][6] Consisting of a 6-degrees-of-freedom spatial kinematic linkage, this device is described as a suitable evaluation tool that quantifies the anteroposterior (AP) load displacement and inversion-eversion (I-E) rotational characteristics of the ankle complex. 3,4,7 The Hollis Ankle Arthrometer has been used in a variety of clinical and research settings involving college-aged athletes and participants less than 25 years of age.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] Valid and reliable measurements of the combined motions within the talocrural and subtalar joints (ankle complex) have been investigated fully and reported using the Hollis Ankle Arthrometer (Blue Bay Research, Inc, Navarre, FL). [3][4][5][6] Consisting of a 6-degrees-of-freedom spatial kinematic linkage, this device is described as a suitable evaluation tool that quantifies the anteroposterior (AP) load displacement and inversion-eversion (I-E) rotational characteristics of the ankle complex. 3,4,7 The Hollis Ankle Arthrometer has been used in a variety of clinical and research settings involving college-aged athletes and participants less than 25 years of age.…”
mentioning
confidence: 99%
“…[3][4][5][6] Consisting of a 6-degrees-of-freedom spatial kinematic linkage, this device is described as a suitable evaluation tool that quantifies the anteroposterior (AP) load displacement and inversion-eversion (I-E) rotational characteristics of the ankle complex. 3,4,7 The Hollis Ankle Arthrometer has been used in a variety of clinical and research settings involving college-aged athletes and participants less than 25 years of age. Researchers have applied this type of arthrometric assessment in studies to biomechanically assess anklecomplex laxity in vivo and in vitro, 3,4,8 identify ankle instability after injury, [9][10][11][12][13] investigate the effects of sex and athletic status on ankle-complex laxity, 14 identify the relationship between ankle and knee ligamentous laxity and generalized joint laxity, 15 investigate the effects of balance training on gait in patients with chronic ankle instability, 13 investigate the effects of limb dominance on ankle laxity, 4 and assess the effectiveness of ankle taping.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Different authors recommended stressing the ankle in dorsiflexion, in the neutral position, or in plantarflexion during the stress manoeuvre [6,10,16,17]. The foot position affects ankle stability because the relationship between ligamentous laxity and bony constraints vary with flexion angle during stress testing [7,9,[18][19][20][21]. Our results showed that mobility of the ankle−hindfoot complex varied as foot flexion angle changed.…”
Section: Discussionmentioning
confidence: 74%